Antimicrbial Effect of Diode Laser and Biossynthesis Silver Nanoparticles on Bactrium Staphylococcus Aureus in Vitro - Sh. Alnayli, Raad; H. Al Hamadani, Adnan; A. Yaseen, Safaa (International Journal of Engineering and Technology, 2018)
The present work was aimed to illustrate how the use of Diode laser or silver nanoparticles (AgNPs) each of them individually, as an antibacterial agent againstÂ  Staphylococcus aureus (S. aureus) as well as study the effective result from the absorption of laser energy by these nanoparticles to kill or inhibition bacterial growth. The silver nanoparticles are prepared by biological method. S. aureus are isolated and identified in the Central Health Laboratory in Al Najaf city. Nanoparticles are tested against S. aureus cultured on Muller Hinton agar but Diode laser or laser with nanoparticles are tested against S. aureus cultured in Nutrient broth. S. aureus are irradiating by Diode laser with different irradiation times, moreover there are different concentrations of AgNPs have been employed for killing and inhibition bacterial growth. Results showed that S. aureus is affected by AgNPs (mainly highest concentration of nanoparticles) also detected that decrease bacterial availability with increase time of irradiation to laser.Â